PENGARUH RISIKO DAN DIVERSIFICATION TERHADAP PROFITABILITAS PADA BANK DEVISA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2016 - Nataly Nataly; Putu Anom Mahadwartha; Mudji Utami (CALYPTRA, 2018)
Abstract- This research aim to analyze factors which affect profitability. Variables which use are credit risk, capital risk, liquidity risk, insolvency risk, bank diversification and bank size. This research use quantitative approach by using multipe linier regression. The sample of this research is the financial company specifically foreign exchange bank that listed in BEI (Bursa Efek Indonesia) for period of 2012-2016. Final samples which are used in this research are equal to 100 observation.